The choice of treated resistant potato varieties to wart in mountain-carpathean region of Ukraine - Shevaga, G.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The potato varieties-differentiators were treated and put into the bank in the conditions in vitro. The enough potato material quantity was accumulated for the next study of the wart potato pathogen differentiations — identifying on variety of differentiators. The potato resistant varieties were treated and chosen. These varieties are perspective for the zonation in mountain-carpathean region of Ukraine in the spreading locations of aggressive pathotypes pathogens.